DOI: 10.25148/etd.fi13042509
|View full text |Cite
|
Sign up to set email alerts
|

Development of Safety Performance Functions for SafetyAnalyst Applications in Florida

Abstract: During the time of my doctoral study at Florida International University, he helped me become a professional, responsible, and confident person. Dr. Gan's influence on my life has spanned many levels, at times as a professor, at other times, like a caring father.Dr. Gan taught me invaluable wisdom and problem-solving skills, both of which have been of great benefit to me during my studies, and will certainly continue to do so as I enter the engineering profession. He even took time out of his busy schedule to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…Both major AADT and minor AADT have a positive relationship with the total crash data, which means an increase in vehicles on the major or minor road is expected to increase the number of crashes. This positive relationship is consistent with the results of the SPF models developed in previous research that developed SPFs specific to Florida ( 4 ). The performance measure results for the rural 3-leg SPF developed in this previous research are mean squared prediction error (MSPE) = 187.14, mean squared error (MSE) = 192.4, and mean absolute deviance (MAD) = 8.21.…”
Section: Developing Spfs For Fdot Context Classification Systemsupporting
confidence: 91%
See 2 more Smart Citations
“…Both major AADT and minor AADT have a positive relationship with the total crash data, which means an increase in vehicles on the major or minor road is expected to increase the number of crashes. This positive relationship is consistent with the results of the SPF models developed in previous research that developed SPFs specific to Florida ( 4 ). The performance measure results for the rural 3-leg SPF developed in this previous research are mean squared prediction error (MSPE) = 187.14, mean squared error (MSE) = 192.4, and mean absolute deviance (MAD) = 8.21.…”
Section: Developing Spfs For Fdot Context Classification Systemsupporting
confidence: 91%
“…A previous study in Florida compared the results of locally calibrated SPFs with the default HSM SPFs. This study used four years of crash data (2007–2010) and developed SPFs for four types of intersections (rural and urban 3-leg and 4-leg) using a negative binomial regression model ( 4 ). Like the other studies, the results showed that the SPFs using Florida-specific calibration factors fit the data better than the models using HSM default values.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Calibration factor is estimated as the ratio of the total number of observed crashes to the total number of predicted crashes calculated using the SPFs and CMFs provided in the HSM. The predictive models are most effective when calibrated to local conditions (Findley et al, 2012;Lu, 2013;Sun et al, 2006;Young and Park, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Calibration factor is estimated as the ratio of the total number of observed crashes to the total number of predicted crashes calculated using the SPFs and CMFs provided in the HSM. The predictive models are most effective when calibrated to local conditions (Findley et al, 2012;Lu, 2013;Sun et al, 2006;and Young and Park, 2013). …”
Section: Table 1-1 Segment and Intersection Types Covered In The Hsm mentioning
confidence: 99%